PENERAPAN SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI (SMKK) PADA PEKERJAAN PENANGANAN JALAN TANAH LUNAK KM 28 BATUAH, KUTAI KARTANEGARA - Yanti Yanti; Syapril Janizar (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
This study discusses the implementation of the Construction Safety Management System (SMKK) in road construction work on soft soil at KM 28 Batuah, Kutai Kartanegara Regency, East Kalimantan. The study aims to analyze geotechnical parameters and construction safety risks under soft soil conditions. The research variables include California Bearing Ratio (CBR), settlement, slope stability, probability, severity, and construction work risk levels. The research methods consisted of field observations, laboratory testing, literature review, and risk analysis using the HIRADC approach within the SMKK framework. The results showed that the soil CBR value ranged from 3–5%, field settlement reached 30–80 cm, and the slope safety factor under saturated conditions was less than 1.0, indicating unstable conditions. Risk analysis identified the main hazards as slope failure, heavy equipment sinking, surface deformation, and occupational accidents, with medium  to high risk levels. The probability level was categorized as frequent due to high rainfall intensity, poor drainage conditions, and heavy traffic loads. The implementation of SMKK through technical and administrative controls, personal protective equipment, geotechnical monitoring, and emergency response systems is necessary to minimize occupational accidents in road construction on soft soil.